Peanut protein – an underutilised by‐product with great potential: a review - Boukid, Fatma (International journal of food science & technology, 2022)
Peanut (Arachis hypogaea L.) is the fourth important oilseed in the world. After oil extraction, defatted peanut is a protein‐rich by‐product containing around 50% of protein that can enable the production of protein isolates (90% protein) and concentrates (70% protein). Peanut protein has an excellent amino acid profile, a desirable volatile profile, a low level of antinutritional factors and a steady supply. Despite these advantages, peanut protein is underutilised because of its poor functional properties caused by the native globular structure and extraction conditions. Nutritional limitations are its deficiency in methionine and lysine and its association with allergic reaction for genetically predisposed subjects. To promote the valorisation of peanut protein in foods, it is very important to ensure a better functionality and a better nutritional value. This review intends to cover the properties of native peanut protein and to discuss innovative strategies including physical, chemical, and biological methods to improve the functionality and to mitigate allergens. These strategies have different degree of success in terms of protein quality and functionality, yield, sustainability and convenience. More investigation is required to select the processing or the combination of processing to boost the application of peanut protein as a valid alternative protein. After deoiling, defatted peanut paste is a protein‐rich byproduct (up to 50% of protein). Recovering peanut protein isolates or concentrates from this paste can boost circular economy and widen the spectrum of plant‐based protein sources. Although peanut proteins have several pros, low functionality and potential allergenicity are limiting factors that can be overcome through suitable strategies.